The Application of Trial as an Adult Concept in Indonesia: Justice for Victims in Juvenile Murder Cases - Christiansen, Nicholas; Bakhtiar, Handar Subhandi (Dinasti Research, 2025)
The increasing incidence of serious crimes committed by juveniles, particularly murder, raises concerns about the adequacy of Indonesia’s juvenile justice system, which emphasizes rehabilitation over retribution. In contrast, the United States applies the